2018
DOI: 10.21608/eajbsf.2018.17019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Teflubenzuron as A Chitin Synthesis Inhibitor Against Spodoptera littoralis Larvae

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…All of the tested insecticides substantially reduced densities of S. recurvalis larvae after the first application, which is in line with several previous studies that have demonstrated their efficacy against lepidopteran larvae [ 29 , 45 , 46 , 47 , 48 , 49 , 50 ]. As re-infestation by S. recurvalis larvae did not occur in any of the plots, including the control, long-term effects of the insecticide treatments to control this pest could not be judged.…”
Section: Discussionsupporting
confidence: 90%
“…All of the tested insecticides substantially reduced densities of S. recurvalis larvae after the first application, which is in line with several previous studies that have demonstrated their efficacy against lepidopteran larvae [ 29 , 45 , 46 , 47 , 48 , 49 , 50 ]. As re-infestation by S. recurvalis larvae did not occur in any of the plots, including the control, long-term effects of the insecticide treatments to control this pest could not be judged.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the present results were in corroboration with various reported results of toxicity of different IGRs against several insects, other than A. ipsilon, such as methoprene against the common house mosquito Culex pipiens (Gelbic et al, 2002), the Asian tiger mosquito Aedes albopictus (Khan et al, 2016), therice meal moth Corcyra cephalonica (Tripathi and Tiwari, 2006), the yellow fever mosquito Aedes aegypti (Braga et al, 2005) and the flesh fly Sarcophagaruficornis (Singh et al, 2017); Flufenoxuron (El-Naggar, 2013), Lufenuron (Bakr et al,2013), Buprofezin (Nasr et al, 2010), Cyromazine (Tananiet al, 2015), Teflubenzuron (Mead and Khedr, 2018) and chlorfluazuron (Shaurub et al, 2020) against the Egyptian cotton leafworm Spodoptera littoralis; pyriproxyfen against the Sunn pest Eurygaster integriceps (Mojaver and Bandani, 2010) and the lawn armyworm Spodoptera mauritia (Resmitha and Meethal, 2016); kinoprene against C. pipiens (Hamaidia and Soltani, 2014); Lufenuron against the red flour beetle Tribolium castaneum (Gadoet al, 2015); Tebufenozide (RH-5992) againstthe Mediterranean flour moth Ephestia kuehniella (Taziret al, 2016); Lufenuron against the lesser mulberry snout moth Glyphodes pyloalis (Aliabadi et al, 2016) and the corn earworm Helicoverpa armigera (Vivan et al, 2017); Fenoxycarb against C. Cephalonica (Begum and Qamar, 2016); Cyromazine against the flies Musca domestica, Stomoxys calcitrans and Fannia canicularis (Donahue et al, 2017); Novaluron against the pink bollworm Pectinophora gossypiella (Ghoneimet al, 2017a) and the mosquito Aedes aegypti larvae (Gunathilaka et al, 2020); Novaluron (Ghoneim et al, 2017b) and Methoxyfenozide (Hamadah and Abo Elsoud, 2018) against olive leaf moth Palpita unionalis; Pyriproxyfen against the false stable fly Muscina stabulans (Hamadah, 2018); etc.…”
Section: Insecticidal Activity Of Pyriproxyfen Against a Ipsilonmentioning
confidence: 99%